Maker-centred in Classroom Learning: Metamorphosis of Primary Education in Malaysia - Balakrisnan, Vijaya; Kamarudin, Nurzatulshima; Ma’rof, Aini Marina; Hassan, Aminuddin (Jurnal Pendidikan Bitara UPSI, 2021)
The paradigm shift from consumer to producer mindset to cultivate transversal competencies other than building a strong foundation in primary education is a major challenge for global educators and researchers. Therefore, as initial efforts, Malaysia has developed and strengthened the reasoning skill as one of the basic skills in primary education. The move to abolish examination by introducing classroom-based assessments has redirected the learning and teaching in the classrooms. Recently, project-based learning, problem-based learning and inquiry-based learning are being studied and applied. However, the rapid growth of hands-on activities has questioned the effectiveness of these learning approaches. Additionally, direct instructions to promote the 21st-century skills and inadequate use of technology, materials and science laboratories in primary schools are still unsolved issues. The smart entrepreneurs have transformed this loophole into a commercial value by creating makerspace or online makers learning for the elite community in Malaysia. This paper attempts to discuss the maker movement in Malaysia with a comparative study on Maker Education to initiate the ideas in Malaysian schools. Theories behind this playful exploration of ideas and materials will be addressed in this study to increase the relevant articles and resources on Maker-centred learning (MCL) in Malaysia. Furthermore, the idea of bridging the Maker concept with STEM education will be explored to turn it into a golden opportunity for researchers and educators to instil future skills with maker-centred learning in the classroom.